The legal standing of artificial intelligence as a legal subject in the modern era: A normative review in the perspective of Indonesian positive law and global comparative law - Wardi, Hilman Ibnu (Privietlab, 2026)
The rapid advancement of Artificial Intelligence (AI) raises a fundamental question in legal science: Can AI be recognized as an independent legal subject? This article examines AI's legal standing within Indonesian positive law and benchmarks it against selected global regulatory frameworks, with primary reference to the EU Artificial Intelligence Act of 2024. This study employs a normative juridical methodology, combining statute, conceptual, and comparative law approaches, applied through a structured four-criterion evaluative framework: rechtsbekwaamheid (capacity to hold rights), handelingsbekwaamheid (capacity to perform legal acts), accountability, and consciousness/free will, deployed consistently across all analytical sections. Primary legal materials include the Civil Code (KUH Perdata), Law No. 28 of 2014 on Copyright, the Electronic Information and Transactions Law (UU ITE) and its amendments, the Personal Data Protection Law (UU PDP), and Regulation (EU) 2024/1689. The findings confirm that AI fails all four framework criteria and cannot be recognized as a legal subject, either as a natural person (natuurlijke persoon) or as a legal entity (rechtspersoon). Under the UU ITE, AI is classified as an 'electronic agent,' and legal responsibility remains vested in its developer, operator, or user. While international scholarship has proposed quasi-legal subject and electronic person concepts, this article critically evaluates rather than merely cautioning against these positions, concluding that neither is suitable for incorporation into Indonesian positive law at the current stage of technological development, as both risk displacing corporate accountability. This article recommends that Indonesia urgently enact a dedicated AI statute adopting a risk-based approach, affirm AI as a legal object, establish an independent regulatory authority, and ensure robust protection of fundamental human rights.